ETR: Jagat Kencana / Ahmad Syakir Yaqzan Ahmad Jafni, Muhd Arieff Saiful Bahar - Ahmad Jafni, Ahmad Syakir Yaqzan; Saiful Bahar, Muhd Arieff (2015)
Jagat kencana Sdn Bhd consist of board director that lead by Ahmad Syakir Yaqzan as Chief Executive Officer (CEO) and being help by four others. First, Muhd Arieff Saiful Bahar, Chief Operating Officer (COO) followed by Muhd Ariff Khalid as Chief Production Officer. Next is Mohd Akmal Mislan, our Chief Marketing Officer and of course we have one that managing our financial, Amira Izzah as Chief Financial Officer. Each of us are share holder to this company of our own.